Pharmaceutical Biotechnology : Integrating Genomics and Emerging Technologies in Modern Drug Development - Arshad Farid; Kifayat Ulllah Shah; Midrar Ullah; Gagan Preet (CRC Press, 2026)
This book examines the role of pharmaceutical biotechnology in modern drug development, highlighting recent advancements in genomics, biopharmaceuticals, and personalized medicine. It explores key molecular and genomic technologies that are revolutionizing drug discovery, design, and delivery. The introductory chapters describe the essential molecular biology techniques, including next-generation sequencing and CRISPR applications, gene editing, synthetic biology, and their role in drug discovery. Furthermore, the book explores pharmacogenomics as a link between genomics and drug response, while also covering the discovery, production, and commercialization of biopharmaceuticals. It provides an in-depth discussion on the role of bioinformatics in analyzing genomic data for drug development, along with genomic strategies for target identification, validation, and the discovery of biomarkers essential to modern drug development. The book also highlights advancements in personalized medicine, emphasizing the use of genomic data to tailor treatments for individual patients. It discusses the design and therapeutic applications of monoclonal antibodies and explores breakthroughs in cell and gene therapies, addressing their potential and the challenges associated with disease treatment.Key Features: Provides a historical and technological perspective on pharmaceutical biotechnology and genomics Explores advanced molecular techniques, including CRISPR and next-generation sequencing, and their applications in drug discovery Discusses pharmacogenomics and the role of biomarkers in enabling personalized medicine Highlights emerging trends such as synthetic biology, gene editing, and biopharmaceutical development Addresses ethical issues and challenges in genomic research and drug development This book is intended for researchers and students of pharmaceutical sciences and biotechnology.The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons [Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND)] 4.0 license.